Human Parasitic Diseases: a Five-Year Literature Review - Al-Tikrity, Dunia Abed Hussein; Abdullah, Hanan Adhawi (Journal of Science in Medicine and Life, 2025)
Parasitic infections remain a pervasive global health challenge, particularly in tropical and resource-limited settings. Recent data show malaria alone accounted for an estimated 263 million cases and 597,000 deaths in 2023[1]. Helminthiases such as schistosomiasis, toxocariasis, and enterobiasis also afflict millions, often as neglected tropical diseases[2]. This review synthesizes findings from 2019–2024 (including dissertations and theses) on key parasites of medical importance, focusing on their life cycles, epidemiology, and host interactions (especially human and animal hosts). A One Health approach is emphasized, as “the boundaries between human, animal, and environmental health are inextricably linked”[3]. We present integrated tables and figures summarizing parasite biology, discuss recent epidemiologic trends, and highlight gaps for future research.